2020
DOI: 10.5194/acp-20-11119-2020
|View full text |Cite
|
Sign up to set email alerts
|

Meteorology-normalized impact of the COVID-19 lockdown upon NO<sub>2</sub> pollution in Spain

Abstract: Abstract. The spread of the new coronavirus SARS-CoV-2 that causes COVID-19 forced the Spanish Government to implement extensive lockdown measures to reduce the number of hospital admissions, starting on 14 March 2020. Over the following days and weeks, strong reductions in nitrogen dioxide (NO2) pollution were reported in many regions of Spain. A substantial part of these reductions was obviously due to decreased local and regional anthropogenic emissions. Yet, the confounding effect of meteorological variabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 15 publications
9
100
0
Order By: Relevance
“…In Europe, reductions of NO 2 are typically slightly larger than we have seen in the UK in our study, perhaps reflecting more stringent lockdown policy. In Spain, NO 2 was reduced by 50 % at both urban traffic and urban background sites (Petetin et al, 2020); in Rome, Turin and Nice, NO 2 was reduced by 46, 30 and 63 %, respectively (Sicard et al, 2020). In all of these studies similarmagnitude increases of O 3 were observed, mainly attributed to the decreased nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 83%
“…In Europe, reductions of NO 2 are typically slightly larger than we have seen in the UK in our study, perhaps reflecting more stringent lockdown policy. In Spain, NO 2 was reduced by 50 % at both urban traffic and urban background sites (Petetin et al, 2020); in Rome, Turin and Nice, NO 2 was reduced by 46, 30 and 63 %, respectively (Sicard et al, 2020). In all of these studies similarmagnitude increases of O 3 were observed, mainly attributed to the decreased nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 83%
“…At the same time, PM 10 mass represents disintegration sources, e.g. windblown soil, crustal rock, mineral and roadside dust, resuspended dust by car movement, agricultural activities in the region, construction work and material wear such as tire abrasion of cars at kerbside sites (Salma and Maenhaut, 2006;Putaud et al, 2010;Harrison et al, 2012;Salma et al, 2020a). They all can be important, particularly under dry weather conditions.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence of the implemented measures, road traffic in many cities worldwide was reduced in a substantial manner and for a considerable time interval. In parallel, lower concentrations of several air pollutants were reported from both satellite observations and in situ measurements (Conticini et al, 2020;Frontera et al, 2020;Keller et al, 2020;Lal et al, 2020;Le et al, 2020;Lee et al, 2020;Liu et al, 2020;Mahato et al, 2020;Morawska and Cao, 2020;Nakada and Urban, 2020;Petetin et al, 2020;Tobías et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Only essential businesses, including grocery stores and food trade, pharmacies, and other industries, were authorized to be open. While other non-essential businesses such as retail shops, bars, restaurants, and commercial companies, had to close [17]. After the lockdown, businesses in some nonessential sectors, including construction and industry, were gradually allowed to return to work.…”
Section: Air Pollution and Meteorological Data Collectionmentioning
confidence: 99%